Deployment of Edge Computing for Smart Healthcare Systems on Cloud Computing Platform - Dipti Chauhan; Jay Kumar Jain; Anuthi Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Improving the productivity of health services is a prime concern for authorities all over the country. Yet, offering patients with scalable healthcare services while cutting costs is a complicated matter. Edge computing technologies and next-generation mobile computing infrastructure are one of the most effective alternatives for integrating efficient healthcare since they can provide real-time and cost-effective patient monitoring systems. Edge computing enables doctors to deliver care to remote areas where connectivity could not be great and skilled healthcare personnel may not be available. The proposed paper discuss the past research work and contribution in the field of smart Healthcare. The Paper further depicts general edge computing architecture for smart Healthcare system and trade-offs of Edge computing. The paper also discuss use cases of smart Healthcare system based on edge computing advantages of Smart- health and the challenges associated with the deployment.